2002
DOI: 10.1590/s0004-282x2002000200004
|View full text |Cite
|
Sign up to set email alerts
|

CT scan findings in mild head trauma: a series of 2,000 patients

Abstract: -The present study describes the cranial computed tomography (CT) scan findings of 2,000 cases of mild head trauma (HT) in Curitiba, Southern Brazil. The mean age of the entire series was 30.8 ± 19 years. The overall male to female ratio was 2:1. The most common causes of head injury were interpersonal aggression (17.9%), falls (17.4%), automobile accidents (16.2%), falls to the ground (13.1%) and pedestrian injuries (13 %). Alcohol intoxication was associated with HT in 158 cases (7.9%). A normal CT scan was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
43
2
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 30 publications
(42 reference statements)
11
43
2
6
Order By: Relevance
“…In fact men prevailed in all age groups from 10 to 79 years. A similar pattern was shown previously by Bordignon and Arruda (2002) in a study of 2000 cases of mild TBI in Brazil. Cassidy et al (2004) reported that men ran about twice the risk of women for mild TBI.…”
Section: Table 5 Proportion Of Intracranial Hemorrhage In Different supporting
confidence: 90%
“…In fact men prevailed in all age groups from 10 to 79 years. A similar pattern was shown previously by Bordignon and Arruda (2002) in a study of 2000 cases of mild TBI in Brazil. Cassidy et al (2004) reported that men ran about twice the risk of women for mild TBI.…”
Section: Table 5 Proportion Of Intracranial Hemorrhage In Different supporting
confidence: 90%
“…4 Routine CT imaging to evaluate mild head trauma in Brazil revealed that about 7.6% had one or more calcifications. 28 Information from four types of studies implicates calcifications as foci of seizures. In unselected persons presenting with seizures residing in endemic countries or in non-endemic regions with high endemic immigrant populations, calcifications are frequently the only abnormality on CT scans and are usually more common than degenerating cysts.…”
mentioning
confidence: 99%
“…Fractures are seen in all the cases of aerocele. Nagy et al 13 found pneumocephalus in 2.6% cases in their series while Bordignon et al 11 and Lee et al 12 detected it in approximately 1.6% cases.…”
Section: Fig 3: Ct Axial Image Showing Extensive Pneumocephalus Withmentioning
confidence: 83%